637 Real-world experience with the new watchman FLX device: data from two high volume sicilian centres. The FLX-iest registry. (8th December 2021) - Vizzari, Giampiero; Mazzone, Paolo; Sardone, Andrea; Laterra, Giulia; Frazzetto, Marco; Sacchetta, Giorgio; Micari, Antonio; Tamburino, Corrado; Contarini, Marco; Carmelo, Grasso
Abstract: Aims: Left Atrial Appendage closure (LAAC) represents a standard therapy for patients with Atrial Fibrillation and contraindication to oral anticoagulation (OAC). The 'Watchman FLX' presented innovative features: higher conformability to LAA shapes, reduced length of the device, closed 'atraumatic' distal end with 'flex-ball' shape during deployment, flattened covered external surface. We report the early 'real-world' experience with the innovative Watchman-FLX device, in two centres at high-procedural volume with consolidated LAAC experience. Methods and results: From May 2019 to January 2021, we enrolled 200 consecutive patients treated with Watchman FLX in a non-randomized double-centre registry. We collected procedural data and followed up the patients for mid-term clinical outcomes. Mean age was 77 ± 7.18 years (67.5% male). Patients presented hypertension in 93% of cases, CKD in 57.5% (mean creatinine level 2 ± 1.1), Diabetes mellitus in 41.5%, Coronary artery disease and Heart failure in 55%. 29% had previous stroke and 56.5 bleeding events. Mean CHA2DS2-VASc was 5 ± 1.40 and HAS-BLED 4 ± 1.01. LAAC indication was: 39.5% of cases symptomatic Haemorrhage, 39% need for Triple antithrombotic therapy, 32% gastro-intestinal bleeding; 18% of patients presented OAC intolerance. TEE guidance was feasible in 186 cases (93%), of which 96 (48%) in general anesthesia and 90 (45%) in conscious sedation (MID-DEX) protocol. 14 ICE cases (7%) were performed in local anesthesia. FLX device repositioning after first attempt was required in 40 cases (20%) without any complication. Device size change, after first choice was needed in eight cases (4%). In one exceptional case simultaneous implant of two Watchman FLX devices was performed in a bi-lobed LAA. Peri-device leak was found in two cases (1%), one solved by changing FLX size (31 to 35 mm). Final procedural success was 99.5%; one unsuccessful case due to LAA reverse chicken-wing with very short depth; no device embolization. Six complications were related to access-site (3%), two cases of combined LAAC-Mitraclip procedure; two major bleedings occurred and one in-hospital death due to hemorrhagic shock (HAS-BLED = 6). At mean follow-up of 272 ± 172.76 days, only 2% of (non-device-related) stroke and 0.6% fatal bleeding resulted. Conclusions: Our registry in a high-risk population treated with the innovative Watchman FLX device, showed high technical procedural success with easy implant and repositioning, no embolization, good LAA sealing and low rate of ischaemic/bleeding complications.